The Relationship Between SpO2 and Laboratory Diagnostic Markers of Cardiovascular Patients with COVID-19 - Ali Bagheri; Naser Kamyari; Maryam Ban; Khadijeh Kanani; Sara Mobarak; Esmat Radmanesh (Disease and Diagnosis, 2023)
Background: In December 2019, a new virus, the coronavirus disease 2019 (COVID-19) was identified as the cause of a cluster of cases of pneumonia of unknown etiology in Wuhan, China. The COVID-19 disease increases cardiovascular events both directly and indirectly. This study aimed to investigate the laboratory diagnostic markers of cardiovascular patients with COVID-19 in Ayatollah Taleghani hospital in Abadan from March 20, 2020 to March 19, 2021. Materials and Methods: This study is a cross-sectional analytical study. Some demographic, laboratory, and clinical information of 200 cardiovascular patients with COVID-19 admitted to Taleghani hospital, Abadan, was received randomly by referring to the medical records section and medical records section and health information system (HIS) as well as searching in the patient records. Inclusion criteria included cardiovascular patients with COVID-19 who had been admitted to Ayatollah Taleghani hospital in Abadan with the diagnosis of a cardiologist and infectious disease specialist, and those whose information was available in HIS. The results were analyzed using SPSS software version 24. Results: The mean age of cardiovascular patients with COVID-19 was reported to be 66.98±18.14. The results revealed that the mean of fasting blood sugar (FBS), serum glutamic oxaloacetic transaminase (SGOT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), creatinine (Cr), blood urea nitrogen (BUN), and erythrocyte sedimentation rate (ESR) was higher than the normal level in these patients. In addition, the mean oxygen saturation (SpO2) was observed to be lower than normal. Reducing the level of SpO2 to less than 90% was significantly related to increasing age, death, patients with a history of lung disease, the duration of hospitalization in ICU, and intubation. This reduction also led to an increase in respiratory rate (RR), LDH, ESR, and C-reactive protein (CRP+1) in cardiovascular patients with COVID-19. Conclusion: In cardiovascular patients with COVID-19, FBS, some kidney markers, liver markers, and inflammatory markers were observed to be higher than normal, and a significant relationship was observed between the reduction of SpO2 and some laboratory diagnostic markers, which requires extensive studies with larger sample size.